If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -20 = 3a Reorder the terms: -20 + 4a = 3a Solving -20 + 4a = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -20 + 4a + -3a = 3a + -3a Combine like terms: 4a + -3a = 1a -20 + 1a = 3a + -3a Combine like terms: 3a + -3a = 0 -20 + 1a = 0 Add '20' to each side of the equation. -20 + 20 + 1a = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 1a = 0 + 20 1a = 0 + 20 Combine like terms: 0 + 20 = 20 1a = 20 Divide each side by '1'. a = 20 Simplifying a = 20
| 0.1y^3+0.3y^3-0.2y^3= | | (9-3)x=30 | | 10y+4=16y-8 | | (a-b)x=c | | 3G+7g=60 | | 0.8+2x=x+3.5 | | 8y-6y=-114 | | -28=-3b | | 2-3z=7z | | 5=9-x | | -9x-2=47 | | z+11=-15 | | 6b-8b=-22 | | =s^2+8s+20 | | 6+n=7*2 | | 3a+6a=27 | | r^2-11=0 | | 2=x/4 | | -5(x+3)=20 | | 5(b+7)=6b | | 11x+18-6x=3 | | 2+3(x-5)=4(x-1) | | 11a-(7a-5)=a-10 | | 4(a-5)=3a | | 3x+45+44-4x=0 | | 3(a+2)=4a | | 4x-9=7x-15 | | (5x+8)-(2x-9)=38 | | 8y+4=4y | | 9y-3=6y | | 9x+99+65-5x=0 | | x*1.55-2.82=x |